Volatile and Odour-Active Compounds of Tuzlu Yoghurt - KAYPAK, DENIZ; KEMAL AVSAR, YAHYA (Asian Journal of Chemistry, 2010)
The objective of this study was to identify volatile and odour-active compounds of Tuzlu yoghurt obtained by direct solvent extraction and high vacuum distillation, based on gas chromatography/mass spectrometer and gas chromatography/ olfactometry. 56 Volatile compounds were identified (7 ketones, 7 aldehydes, 5 esters, 14 alcohols, 3 terpenes, 4 lactones, 4 miscellaneous and 12 free fatty acids) by gas chromatography/ mass spectrometery and 6 (1 ketone, 4 aldehydes and 1 sulphurous compound) by gas chromoatography/olfactomatery. 29 Compounds were found to be odour-active. Ethyl butanoate, methional in neutral/basic fraction and ethanoic, butanoic and hexanoic acids in the acidic fractions appeared to be the most potent odour-active compounds. The detection of odour-active compounds by this study may be promising for the certification of traditional yoghurt products as Protected Designation of Origin.